Acute myeloid leukemia and clonal chromosome aberrations in relation to past exposure to organic solvents - Albin, Maria; Björk, Jonas; Welinder, Hans; Tinnerberg, Håkan; Mauritzson, Nils; Johansson, Bertil; Billström, Rolf; Strömberg, Ulf; Mikoczy, Zoli; Ahlgren, Tomas; Nilsson, Per-Gunnar; Mitelman, Felix; et al. (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'The effects of occupational and leisure-time exposures on the risk of acute myeloid leukemia (AML) were investigated with emphasis on clonal chromosome aberrations (CCA) and morphological subtypes.' ' METHODS ': 'Consecutively diagnosed cases of AML (N=333) and 1 population referent per case were retrospectively included in the study. Information on worktasks, companies, and leisure-time activities was obtained with telephone interviews. Exposure probability and intensity were assessed by occupational hygienists. Associations were evaluated with logistic regression.' ' RESULTS ': 'Exposure to organic solvents was associated with an increased risk of AML [low exposure: OR 1.5 (95% confidence interval (95% CI) 1.0-2.3, moderate-high exposure: OR 2.3 (95% CI 1.0-5.0)]. For exposure to solvents, but not to benzene, the OR was 1.2 (95% CI 0.69-2.0) for "low" and 2.7 (95% CI 1.0-7.3) for "moderate-high" exposure. The observed effects increased with intensity and duration of exposure. The estimated effects were higher for patients >60 years of age at the time of diagnosis. The effect of exposure to organic solvents was not differential with regard to morphology [except possibly erythroleukemia: OR 4.2, 95% CI 1.0-17 or the presence of CCA in general]. No increased risk for AML with complex CCA or with total or partial losses of chromosomes 5 or 7 were observed, but a higher risk was found for AML with trisomy 8 (OR 11, 95% CI 2.7-42) as the sole aberration.' ' CONCLUSIONS ': 'Exposure to organic solvents was associated with an increased risk of AML. This association was not due to benzene exposure alone and may be modified by age. Furthermore, specific associations with trisomy 8, and possibly also erythroleukemia, were suggested.
Keywords: age; benzene; case-referent study; cytogenetic; effect modification; erythroleukemia; occupational limit value; population attributable risk; trisomy 8